Bridgeless interleaved boost PFC converter with variable duty cycle control - E Silva, Luciano S.C. [UNESP] (2011)
This paper proposes a bridgeless boost interleaved PFC (power factor correction) converter with variable duty cycle control. The application of bridgeless technique causes reduction of conduction losses, while the interleaving technique of converters cells allows division of efforts in semiconductor devices and reduction of weight and volume of the input EMI filter. The use of variable duty cycle control has the functions of regulating the output voltage and eliminating the low order harmonic components that appears in the input current of the common interleaved power factor converters working in Discontinuous Conduction Mode (DCM). The simulation results of the proposed converter presented high power factor and a good transient response in relation to the output voltage regulation in presence of high load variations and supply voltage variations. © 2011 IEEE.